Untargeted Salivary Metabolomics and Proteomics: Paving the Way for Early Detection of Periodontitis - Mariacristina Amato; Alessandro Polizzi; Andrea Blasi; Cristina Grippaudo; Gaetano Isola (Applied Sciences, 2025)
Periodontitis is a chronic inflammatory disease that affects the supporting structures of the teeth and is a major cause of tooth loss worldwide. Early detection is critical to prevent disease progression and avoid irreversible tissue damage. Saliva, a non-invasive, easily accessible biological fluid, has emerged as a promising diagnostic tool for the early detection of various diseases, including periodontitis. This narrative review explores the potential of untargeted salivary metabolomics and proteomics in identifying biomarkers for the early diagnosis of periodontitis. Unlike traditional targeted approaches, untargeted analyses allow for the comprehensive exploration of a wide range of metabolites and proteins, without predefined hypotheses. This approach provides a deeper understanding of the disease’s biochemical landscape and can reveal novel biomarkers associated with the inflammatory processes of periodontitis. Besides making an early diagnosis, detecting specific biomarkers of periodontitis may enable the clinician to make an extremely personalized treatment plan. The review highlights key findings in the field, discusses the challenges and limitations of these techniques, and presents future perspectives on how salivary metabolomics and proteomics could revolutionize early diagnostic strategies in periodontal management.